PERAN ORANG TUA DALAM MENGAJARKAN LITERASI KEUANGAN PADA ANAK USIA DINI - Fajarrini, Arsyia; Amalia Rabiatul Adwiah (EDUCHILD (Journal of Early Childhood Education), 2025)
There are still many Indonesian people who do not know about financial literacy, only 29.7% of the total population. Instilling financial literacy needs to be introduced early on to improve the ability to manage finances when they are adults. The purpose of this study is to provide insight that financial literacy needs to be instilled early on. The research method uses literature studies or is called library research. The results of the study show that the role of parents is very important in introducing financial literacy to early childhood. This is because parents are the first and main education, so the role of parents is very much needed. The role of parents can be done by introducing the concept of money, introducing saving, inviting them to go shopping or inviting them to financial institutions. That way, children can manage their finances properly when they are adults, so that they can avoid children from financial weaknesses